The Financial Times guide to bond and money markets - Arnold, Glen (Pearson, 2015)
This jargon-busting book shows how bond & money markets work & how they impact on everyday life. Understand terms & products Explore types of markets & their functions Discover factors influencing market prices Learn how fluctuations can affect your money strategies